Pengaruh Kepemimpinan dan Budaya Organisasi Terhadap Kinerja Pegawai Pada Dinas Sosial Kota Serang - Suhendi, Ipan (Pascasarjana Universitas Primagraha, 2022)
This study aimed to determine the influence of leadership and organizational culture in improving employee performance at the Serang City Social Service. The research method used in this study is a quantitative approach, a descriptive method used to describe the nature or characteristics of a particular phenomenon, and a verification method used to determine the relationship between two or more variables. In comparison, the data collection technique used is a questionnaire. The population used is 34 respondents. Furthermore, the data was processed using descriptive and statistical analysis of values which was carried out using SPSS software version 26. From these calculations, the correlation coefficient value is R = .859, which indicates a relationship between leadership and organizational culture on employee performance. If leadership and organizational culture are carried out well, it will affect positive employee performance. All hypotheses are accepted, either partially or simultaneously.